Nucleoside diphosphate kinase B-activated intermediate conductance potassium channels are critical for neointima formation in mouse carotid arteries significance - Zhou, Xiao-Bo; Feng, Yuxi; Borggrefe, Martin; Wieland, Thomas (Arteriosclerosis, thrombosis, and vascular biology, 2015)
Objective: Vascular smooth muscle cells (VSMC) proliferation is a hallmark of atherosclerosis and vascular restenosis. The intermediate conductance Ca2+-activated K+ (SK4) channel is required for pathological VSMC proliferation. In T lymphocytes, nucleoside diphosphate kinase B (NDPKB) has been implicated in SK4 channel activation. We thus investigated the role of NDPKB in the regulation of SK4 currents (ISK4) in proliferating VSMC and neointima formation. Approach and Results: Function and expression of SK4 channels in VSMC from injured mouse carotid arteries were assessed by patch-clamping and real-time polymerase chain reaction. ISK4 was detectable in VSMC from injured but not from uninjured arteries correlating with the occurrence of the proliferative phenotype. Direct application of NDPKB to the membrane of inside-out patches increased ISK4, whereas NDPKB did not alter currents in VSMC obtained from injured vessels of SK4-deficient mice. The NDPKB-induced increase in ISK4 was prevented by protein histidine phosphatase 1, but not an inactive protein histidine phosphatase 1 mutant indicating that ISK4 is regulated via histidine phosphorylation in proliferating VSMC; moreover, genetic NDPKB ablation reduced ISK4 by 50% suggesting a constitutive activation of ISK4 in proliferating VSMC. In line, neointima formation after wire injury of the carotid artery was substantially reduced in mice deficient in SK4 channels or NDPKB. Conclusions: NDPKB to SK4 signaling is required for neointima formation. Constitutive activation of SK4 by NDPKB in proliferating VSMC suggests that targeting this interaction via, for example, activation of protein histidine phosphatase 1 may provide clinically meaningful effects in vasculoproliferative diseases such as atherosclerosis and post angioplasty restenosis.